QTc Interval in Adolescents and Young Athletes: Influence of Correction Formulas - Gervasi, Salvatore Francesco; Bianco, Massimiliano; Palmieri, Vincenzo; Cuccaro, Francesco; Zeppilli, Paolo (International Journal of Sports Medicine, 2017)
A QTc interval at the upper limits in young athletes can be challenging. Regardless of factors able to influence it (age, electrolytes, etc.), several authors underlined that rate correction formulas can often underestimate/overestimate it. Our objective was to identify the most reliable formula and relative upper normal limit of QTc for this population. The rest ECG of 701 healthy elite male athletes was analyzed. QTc was calculated with 4 formulas (Bazett, Fridericia, Framingham, Hodges). Correlation/regression analysis of QTc vs. heart rate and upper limits were calculated and compared considering different age groups. Abnormal ECGs were compared considering different upper limits. Correlation between QTc and heart rate was highly significant using Bazett’s and Framingham’s formulas, lower using Hodges’ formula, and not significant using Fridericia’s formula. Except for Framingham’s, the number of abnormal ECGs was identical considering an upper limit of 480 msec, and significantly different for lower limits. Upper limits were: Bazett 469 msec, Fridericia 451 msec, Framingham 458 msec, and Hodges 461 msec. Except for Framingham’s, no difference among other formulas in individuating abnormal ECGs for QTc≥480 msec was found. QTc obtained with the Bazett’s formula appears highly dependent on heart rate. This, especially in the grey zone (440–480 msec), can lead to overtesting. Framingham’s formula shows similar limits. Hodges’ formula offers uncertain reliability. Fridericia’s formula seems the most reliable.
Keywords: ECG; sudden death; Bazett; Fridericia; Long QT; LQTS